DEVELOPMENT OF BETAWI GAMBANG BREAD PRODUCTS WITH THE ADDITION OF SORGUM FLOUR AND RED SPINACH AS A MEANS OF UTILIZING LOCAL FOOD INGREDIENTS - Mochammad Akbar; Alicia Siti Amanah (JURNAL MANAJEMEN KULINER, 2026)
This study aims to develop functional Gambang Betawi Bread with partial substitution of wheat flour using sorghum flour (Sorghum bicolor) and red spinach fortification (Amaranthus tricolor L.). This effort was made to utilize local food ingredients rich in nutrients and support food diversification. The research method used was an experimental Completely Randomized Design (CRD) design, involving two treatment formulas: F1 (Sorghum:Wheat 50:50) and F2 (Sorghum:Wheat 75:25). Hedonic tests were conducted by 15 semi-trained panelists using a 5-point Likert scale, followed by Kruskal-Wallis analysis. The results of the sensory test showed that Formula 1 (F1) received the highest acceptance in taste (average 4.27) and texture (average 4.40) in the 'Like' category. Although there was a significant difference in color attributes (P<0.05), there was no significant difference in taste, aroma, and aftertaste between F1 and F2. Calculation of the nutritional content per serving (100g) showed an increase in fiber (1.8g) and protein (7.4g). It was concluded that Formula 1 was the best formulation accepted by the panelists and was feasible for commercial development, with a selling price of Rp9,515 per serving (35% margin).